PRECEPTION OF STUDENTS OF PGSD STUDY ON MOODLE AS LMS DURING THE COVID-19 PANDEMIC - cici Simbolon (Jurnal Scientia, 2021)
The learning process in Indonesia runs online due to the impact of the covid 19 pandemic. The onlinelearning process is carried out through an LMS, namely Moodle. The data collection tool used todetermine the perceptions of elementary school teacher education study program students is throughthe provision of a questionnaire totaling 10 items. From the results of the analysis and interpretation,the following data were obtained, 40.9% of students were enthusiastic in participating in the learningprocess using Moodle during the covid 19 pandemic, 40.9% were happy in the learning processintegrated with Moodle, 50% felt happy to get good grades through Moodle application, 45.45% ofstudents feel unburdened in doing the tasks given through the Moodle application, 50% of studentsfeel happy in doing assignments independently in the COVID-19 pandemic situation, 40.9% ofstudents feel interested in using Moodle applications, 40, 9% of students feel enthusiastic if the lectureasks questions through Moodle, 50% of students feel normal or neutral to Moodle because it providesinteresting and diverse features, 40.9% of students find it easy to use Moodle applications, 40.9% ofstudents understand the use of Moodle after being explained by the lecture.